Livelihood Improvement of Small and Marginal Farmers Through Integrated Approach of Broiler Rabbit Production in North-east India - Khan, M. H.; Kumar, Suresh; Kadirvel, G.; Basumatary, R.; Bharti, P. K.; Dubal, Z. B. (International Journal of Bio-resource and Stress Management, 2023)
As an alternative to broiler chicken, rearing rabbits for meat and fur skins is gaining momentum now a days because of the fact that the meat from rabbit is low in cholesterol and the most delicious. Rabbits were reared as laboratory animals till 1970. Commercial aspects of rabbit rearing started after the import of exotic rabbits during 1970s by CSWRI, Indian Council of Agricultural Research for the first time in our country. Rabbits are the only ‘Micro livestock’ suitable for rearing by small farmers and landless agricultural laborers with simple housing in their backyards and can be fed with forages, agricultural by-products and kitchen wastes. In fact backyard rabbitries are best suited for our country to increase the per capita income and per capita animal protein availability.